Understanding the SES gradient in health among the elderly: The role of childhood circumstances - Till Stowasser; Florian Heiss; Daniel McFadden; Joachim Winter (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2014)
Individuals' socioeconomic status (SES) is positively correlated with their health status. While the existence of this gradient may be uncontroversial, the same cannot be said about its explanation. In this paper, we extend the approach of testing for the absence of causal channels developed by Adams et al. (2003), which in a Granger causality sense promises insights on the causal structure of the health-SES nexus. We introduce some methodological refinements and integrate retrospective survey data on early childhood circumstances into this framework. We confirm that childhood health has lasting predictive power for adult health. We also uncover strong gender differences in the intertemporal transmission of SES and health: While the link between SES and functional as well as mental health among men appears to be established rather late in life, the gradient among women seems to originate from childhood circumstances.
urn:nbn:de:bvb:19-epub-20847-3
Keywords: C33; I0; I12; 330; health; wealth; socio-economic gradient; causal inference; Granger causality; individual heterogeneity; childhood health; childhood circumstances